Detecting delirium: a systematic review of ultrabrief identification instruments for hospital patients - Liu, Yadong; Li, Zhenzhen; Li, Ying; Ge, Ning; Yue, Jirong (Frontiers in Psychology, 2023)
Objective: Early identification of delirium, which often occurs in older patients, can effectively reduce adverse prognoses. One way to increase the detection rate of delirium is to use an effective ultrabrief instrument for higher-frequency screening. The purpose of this review is to evaluate the diagnostic accuracy of ultrabrief screening tools for delirium. Methods: The Cochrane Library, PubMed and EMBASE were searched from January 1, 1974, to November 31, 2022. We assessed the measurement properties of screening instruments using the consensus-based standards for selecting health measurement instruments (COSMIN) checklist and evaluated the risk bias of the included studies using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. The diagnostic test accuracy of instruments for delirium was reported using sensitivity, specificity, positive likelihood ratio (PLR) and negative likelihood ratio (NLR). Result: Of the 4914 items identified, 28 met the eligibility criteria, resulting in 5 different delirium identification tools. The overall study quality assessed by the QUADAS-2 tool was moderate to good. Of the five screening tools, two instruments had sensitivity ≥80% and specificities ≥80%: 4AT and UB-2. The most comprehensive is the 4AT scale, which has a sensitivity of 0.80 [95% confidence interval (CI):0.68, 0.88] and a specificity of 0.89 [95%CI: 0.83, 0.93] and contains 4 items. UB-2 has a sensitivity of 0.88 [[95%CI: 0.72, 0.96] and a specificity of 0.64[[95%CI: 0.56, 0.70]. Conclusion: UB-2 and MOTYB had excellent sensitivity for delirium screening at an early stage. In terms of sensitivity and intentionality, the 4AT is the best recommended scale.